ANALISIS KESULITAN BELAJAR MATEMATIKA DALAM MATERI KPK DAN FPB PADA SISWA KELAS V SDN WANASARI 13 - Nur Fadillah, Indriani; Anggraeni Maharbid, Dian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study aims to describe the various forms of difficulties students experience in studying the KPK and FPB materials at math lessons. This type of research is qualitative with a case study approach. The study was done on student v. SDN university students 13 with the subject number 5 girls and 3 boys. This research data retrieval through interviews and tests. It is known that most students have not reached minimum minimum standardized criteria (KKM) asa result of their lack of understanding of basic mathematical concepts, especially those of multiplication. The main difficulty found included counting skills, such as having not mastered the multiplication and errors in the use of prime Numbers in the tree factor. In addition, students also experience problems in problem solving, which are marked with inability to distinguish between types of KPK or FPB and confusion in the step of completion. It may be concluded that lack of basic concept mastery and problem solving capabilities is a major factor that hinders students from completing the story problem in the KPK and FPB materials.